Undang-undang Kawalan Penjualan Arak oleh Pihak Berkuasa Tempatan: Kajian Khusus di Negeri Selangor Darul Ehsan (Kanun: Jurnal Undang-undang Malaysia, 2012)
Prohibition of alcoholic drinks to Muslims, whether the act of drinking or involvement with any activities related to alcoholic drinks is very clear according to Islamic law. The main purpose of this study was to analyze the the role of the local authorities and effectiveness in limiting the sale of alcoholic drinks to Muslims in Selangor and the challenges or obstacles faced by the local authorities in Selangor to control the sale of alcoholic drinks. Data and information based on feedback from 12 local authorities in Selangor were collected from the licensing and enforcement department. The results showed that all local authorities in Selangor control the sale of alcoholic drinks to Muslims by imposing supplementary conditions in approving the licence of premises which sell alcoholic drinks and also through the self-regulatory system introduced by the Selangor State Government. At the same time, the local authorities also face many constraints in enforcing the laws that control the sale of alcoholic drinks, particularly in terms of legal conflicts and enforcement barriers. Therefore, several recommendations and suggestions for improvement are deemed necessary for the realization of an effective law in limiting the sale of alcoholic drinks involving Muslims in Selangor.Keywords: Islamic Criminal Law, controlling the sale of liquor, Local Council, self-regulatory system